A study on delayed cord clamping and early skin-to-skin contact and its effects on neonatal outcome - Nee Laxmi Sharma, Laxmi Dixit; Gayadin, Yadav Sushilkumar; Sangeeta Kansal; Sinha, Shuchi Jain; Jain, Madhu (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Previous study conducted against immediate tying and cutting of the umbilical cord and suggested waiting until the child had taken repeated breaths and the pulsation in the cord had ceased to prevent potential weakness in the child. A comparative study between delayed cord clamping (DCC) and early cord clamping (ECC) was carried out on a select group of primigravida without any high-risk factor and delivering at term. The objective of the study was to identify the effects of delayed cord clamping and early skin to skin contact on new born infant’s physiological parameters (temperature, weight, SpO2= saturation of peripheral oxygen, Apgar score= appearance, pulse, grimace, activity, and respiration, Hb=haemoglobin level). Methods: Study sample consisted of 300 mothers and their new born after gaining mother’s acceptance. They were divided into 2 groups of 150 each. Group A underwent delayed cord clamping and early skin to skin contact and group B early cord clamping. Newborns monitored 24 hours for hypothermia, apnoea, oxygen needs. Results: The findings of the present study were equivalent among both groups regards the mean neonatal haematological parameters were comparable and slightly elevated hemoglobin level and weight status among late cord clamping compared to early cord clamping group with significant difference was observed at 24 hour later. Conclusions: This study was found that DCC does have a beneficial effect on temperature, Apgar score, SpO2, Hb level and weight status of new born. Therefore, it is believed that DCC and early skin to skin contact (ESSC) provides effective thermal control with a reduced risk of hypothermia.